Analysis of Production Factors for The Rubber Smallholder Sector in Malaysia (Journal of Entrepreneurship and Business, 2021)
The production of natural rubber in Malaysia is primarily dominated by smallholders representing almost 95% of the total rubber plantation, while commercial estates constitute the remainder. The natural rubber industry is an integral part of the Malaysian economy, with 2.6% of with the total contribution of exports valued at more than RM20 billion annually. Therefore, the three key inputs that affect the productivity of smallholders in all states throughout Malaysia should be critically explored There is limited literature on the production of rubber by smallholders. The labour consumption, land area and adherence to agronomic practices are the main inputs and variables in this study. The Ordinary Least Square (OLS) was used to analyse the correlation of each input with rubber production by referring to the concept of the production function. The results discovered that 96% of rubber production yields are explained by independent variables consisting of labour, plantation area, weeding and cultivating activities. Furthermore, the total plantation area and adherence to agronomic practices positively affect total rubber production, while inefficient use of labor negatively affects total rubber production
Keywords: Array; Array; Array; Array